DETERMINANTS OF MALNUTRITION AMONG CHILDREN UNDER FIVE YEARS IN PAGER DIVISION, KITGUM MUNICIPALITY, KITGUM DISTRICT: A DESCRIPTIVE CROSS-SECTIONAL STUDY - Onyach , Richard; Turumanya , Judah; Nalubega, Jane Frank (Student’s Journal of Health Research Africa, 2023)
Background The major objective of the study was to assess the determinants of malnutrition among children under five years in pager division Kitgum municipality. The specific objectives of the study were to: determine wasting, establish the feeding practices associated with wasting and to establish socio-economic factors associated with wasting among children under five years at Pager Division Kitgum Municipality. Methodology This study adopted a descriptive cross-sectional study designed for children under five years among households in pager division kitgum municipality where 150 mothers of children selected using random sampling were interviewed. Data was collected using questionnaires, analyzed using Epi Info program and bi-variate analysis was used to determine the associated factors of wasting among children under five years. Results Results from the study analysis also confirmed that how the child caretaker fed the child after six months, the type of food fed to a child at a meal, the amount the child’s caretaker earned per month, occupation of the mother, mother’s level of education, and the number of children under five years in a household were the most significant factors which affect malnutrition in children who were below 5 years of age in Kitgum Municipality. Conclusion Results from the study confirmed that malnutrition was still high among children under five in pager division Kitgum Municipality with wasting standing at 17.3% and high among children aged 6-11 months at 6%. Recommendations The study recommended community nutritional interventions to address the root causes of malnutrition in regard to wasting. Further research is needed to obtain explanation regarding sex differentials with wasting across socio-economic strata Similar community-based studies in the area of child nutrition is needed to determine the root causes of socio-economic and cultural drivers of malnutrition